The crew timetabling problem: an extension of the crew scheduling problem - Gomes, Marta Castilho (2011)
In some urban transportation companies driving periods are short when compared with the total duty time, leading to long non-driving periods that can be used as cover time. This paper presents the Crew Timetabling Problem, an extension of the Crew Scheduling Problem in which crew timetables are obtained by levelling the cover crew resources. An objective function for this problem is proposed in order to balance the number of driving and cover crews. A Lisbon Underground case study is used to illustrate The Crew Timetabling Problem. The problem is represented in a multigraph and solved by a tabu search-based heuristic.